Exchange current density of reversible solid oxide cell electrodes. (30th April 2022) - Fukumoto, Takuro; Endo, Naoki; Natsukoshi, Katsuya; Tachikawa, Yuya; Harrington, George F.; Lyth, Stephen M.; Matsuda, Junko; Sasaki, Kazunari
Abstract: Reversible solid oxide cells (r-SOCs) can be operated in either solid oxide fuel cell or solid oxide electrolysis cell mode. They are expected to become important in the support of renewable energy due to their high efficiency for both power generation and hydrogen generation. The exchange current density is one of the most important parameters in the quantification of electrode performance in solid oxide cells. In this study, four different fuel electrodes and two different air electrodes are fabricated using different materials and the microstructures are compared. The temperature, fuel humidification, and oxygen concentration at the air electrode are varied to obtain the apparent exchange current density for the different electrode materials. In contrast to ruthenium-and-gadolinia-doped ceria (Rh-GDC) as well as nickel-and-gadolinia-doped ceria (Ni-GDC) electrodes, significant differences in the apparent exchange current density were observed between electrolysis and fuel cell modes for the nickel-scandia-stabilized zirconia (Ni-ScSZ) cermet. Variation of gas concentration revealed that surface adsorption sites were almost completely vacant for all these electrodes. The apparent exchange current densities obtained in this study are useful as a parameter for simulation of the internal properties of r-SOCs. Graphical abstract: Image 1 Highlights: Reversible solid oxide cells with different electrode materials were fabricated. Apparent exchange current densities and activation energies were quantified. Ceria was found to accelerate the electrochemical reactions in electrolysis mode. Surface adsorption sites on the electrodes were found to be largely vacant.